Duby: uma perspectiva histórica sobre as mulheres medievais - Costa, Milton Carlos [UNESP] (My University, 2012)
This paper will discuss the wedding in the historical conditions of feudalism, and mainly, summarize partially the book Heloise and Isolde and other ladies of the twelfth century, in which the author provided an historical condition significant, exploring of an original manner the documents known. Then we will see as important medievalists have studied the issues addressed by Duby as kinship, sexuality, male and female, and that were the object of our work, serving as a counterpoint to them.

Neste trabalho trataremos do casamento nas condições históricas do feudalismo e, principalmente, sintetizaremos parcialmente o livro Heloísa e Isolda e outras damas do século XII, no qual o autor proporcionou uma contribuição historiográfica significativa, explorando de maneira original documentos em geral conhecidos. Depois veremos como a melhor medievalística contemporânea estudou temas abordados por Duby como o parentesco, a sexualidade, o masculino e o feminino, e que foram objeto de nosso trabalho, servindo de contraponto aos mesmos.
Duby: a historical perspective on medieval women
Keywords: Kinship; Sexuality; Medievalística; Parentesco; Sexualidade; Medievalística